Monte Carlo Simulation of Counting Experiments - Ogden, Philip M. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
A computer program to perform a Monte Carlo simulation of counting experiments was written. The program was based on a mathematical derivation which started with counts in a time interval. The time interval was subdivided to form a binomial distribution with no two counts in the same subinterval. Then the number of subintervals was extended to infinity to form the Poisson distribution. Under restricted conditions the Gaussian (normal) distribution can approximate the Poisson. The computer program was written in the BASIC and FORTRAN languages and generates a pseudo-random number for each subinterval. These generated numbers are then compared with the Poisson and Gaussian distributions. A graphical display of the results is part of the program. A sample output is supplied in an appendix. (WH)
ERIC Note: Paper presented at the Rochester Area Colleges Workshop on the Use of Computers in Instruction (Rochester, New York, October 23, 1973).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computation; Computer Programs; Computer Science; Experiments; Mathematical Models; Monte Carlo Methods; Probability; Statistics; Speeches/Meeting Papers